Predictive value of tip-apex distance and calcar-referenced tip-apex distance for cut-out in 398 femoral intertrochanteric fractures treated in a private practice with dynamic intramedullary nailing - Barra, Amariel E.; Barrios, Carlos (Frontiers in Surgery, 2024)
Biomechanical complications such as cut-out is one of the most common causes of internal fixation failure of trochanteric hip fractures. The tip-apex distance (TAD), and the calcar-referenced tip apex distance (CalTAD) have been suggested as the radiographic parameters that most predict the risk of cut-out. The purpose of this study was to check is these two factors could predict implant cutout in a series 398 of intertrochanteric hip fractures, treated by dynamic intramedullary nailing with the Trigen Intertan short nail. We reviewed 398 consecutive intertrochanteric fractures included in a prospective study, and treated in a single private hospital by the same surgeon. The overall cutout rate was 2.3% (9/398). The significant parameters in the univariate analysis were AO fracture type, quality of fracture reduction (p = 0.02), tip-apex distance (TAD) (p < 0.001), CalTAD (p = 0.001), and quality of reduction. No statistically significant relationships were observed between the occurrence of cut-out and gender, age, fracture side, and ASA type. Multivariate analysis showed that only TAD showed independent significant relationship to cut-out (p <0.001). In this study CalTAD has not predictive value in the multivariable analysis. Our findings differed from previous reported studies suggesting that CalTAD is best predictor of cut-out. According to our data, careful optimal reduction ensuring stable fixation with TAD > 25 mm reduced the occurrence of cut-out after dynamic intramedullary nailing of intertrochanteric fractures.